Improving flotation separation of apatite from dolomite using PAMS as a novel eco-friendly depressant - Yang, Bin; Zhu, Zhanglei; Sun, Haoran; Yin, Wanzhong; Hong, Jongsu; Cao, Shaohang; Tang, Yuan; Zhao, Chen; Yao, Jin (Minerals engineering, 2020)
[Display omitted] •Flotation separation of apatite and dolomite is very difficult using NaOl alone.•PAMS is selectively adsorbed onto dolomite due to its strong bonding to Mg sites.•The adsorption of NaOl onto dolomite is hindered strongly by the addition of PAMS.•Greater amounts of NaOl is adsorbed on apatite than dolomite in the presence of PAMS.•Flotation separation of apatite from dolomite can be realized by PAMS. Froth flotation is widely used as an effective method for separating apatite from dolomite. However, it is of difficulty to realize the efficient separation of apatite and dolomite using the traditional fatty acid collectors without any depressants due to their similar physicochemical properties. In this work, the depression performance of poly (acrylic acid-co-maleic acid) sodium salt (PAMS) acting as a new depressant was evaluated via the flotation experiments, when sodium oleate (NaOl) was employed as the collector. The results from flotation experiments illustrated that PAMS effectively depressed the dolomite flotation whereas it exhibited weak influences on the floatability of apatite. It was also found that the reagent scheme of 14 mg/L PAMS and 100 mg/L NaOl could effectively remove dolomite from apatite at pH 9.00. Moreover, the adsorption mechanism of PAMS onto the two minerals was uncovered through the surface analyses. The analyzed results indicated that the interaction of PAMS with magnesium ions exposed to dolomite played a vital part in the selective adsorption of PAMS onto dolomite. Magnesium, as a major component of dolomite rather than apatite, enhanced the chemisorption of PAMS onto dolomite. Furthermore, the larger pre-adsorption of PAMS onto dolomite than apatite significantly led to the much less adsorption of NaOl on the dolomite surface, thereby reducing the hydrophobicity of dolomite in NaOl system and intensively depressing the dolomite flotation. Therefore, PAMS can be utilized as a potential depressant for removing dolomite from apatite by direct flotation.